2007
DOI: 10.1038/sj.gene.6364412
|View full text |Cite
|
Sign up to set email alerts
|

Association between RANTES functional polymorphisms and tuberculosis in Hong Kong Chinese

Abstract: Chemokines play a major role in leukocyte recruitment during the formation of tuberculous granulomas. We studied the association between genetic polymorphisms of three chemokines, monocyte chemoattractant protein-1 (MCP-1), RANTES (regulated on activation, normal T cell expressed and secreted) and macrophage inflammatory protein-1a (MIP-1a), and tuberculosis (TB). The distribution of five functionally significant single-nucleotide polymorphisms (SNPs), MCP-1 À2518A/G, RANTES À403G/A, À28C/G and In1.1T/C as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 20 publications
3
62
3
Order By: Relevance
“…A few studies have focused on Ϫ403G/A and Ϫ28C/G promoter variants of the RANTES gene (Table 1), providing evidence that genotypes or haplotypes derived from a combination of SNPs could confer resistance or susceptibility to TB (26,45,192). However, the actual causative variants need to be established before definitive conclusions can be made.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…A few studies have focused on Ϫ403G/A and Ϫ28C/G promoter variants of the RANTES gene (Table 1), providing evidence that genotypes or haplotypes derived from a combination of SNPs could confer resistance or susceptibility to TB (26,45,192). However, the actual causative variants need to be established before definitive conclusions can be made.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…In contrast, no association of MCP-1 -2581 was found in Brazilian multicase families [41] and in a Chinese patient group from Hong Kong. [42] In the present study, it was found that the white subjects had no significant differences in frequency of the G and A alleles compared with black subjects. One can believe that, at present, the overall data do not sufficiently support any major involvement of that variant in TB susceptibility or protection.…”
Section: Discussionmentioning
confidence: 77%
“…The African group included 5 studies [Buijtels et al, 2008;Möller et al, 2009;Thye et al, 2009;Velez Edwards et al, 2012 (2 case-control (Ben-Selma et al, 2011;Hussain et al, 2011;Arji et al, 2012). The Asian group included 10 studies (Flores-Villanueva et al, 2005;Chu et al, 2007;Alagarasu et al, 2009;Xu et al, 2009;Yang et al, 2009;Feng et al, 2011;Naderi et al, 2011;Mishra et al, 2012;Zhang et al, 2012;Singh et al, 2014). All studies analyzed the association between MCP-1 -2518A/G polymorphisms and human TB susceptibility.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%